Diet and Abdominal Autofluorescence Detected by in Vivo Fluorescence Imaging of Living Mice - Yusuke Inoue; Kiyoko Izawa; Shigeru Kiryu; Arinobu Tojo; Kuni Ohtomo (Molecular Imaging)
We investigated the effect of diet on abdominal autofluorescence detected by in vivo fluorescence imaging (FLI) of living mice. Groups of mice were fed a regular, alfalfa-free, or purified diet, and whole-body FLI was performed without the administration of fluorescent probes. In addition, quantum dots were injected intravenously into mice fed one of the three diets, and FLI was performed 3 and 24 hours later. Intense autofluorescence originating from the animals' intestinal contents was observed in mice fed the regular diet. Intestinal autofluorescence decreased substantially after feeding with the alfalfa-free diet and further after feeding with the purified diet. The decline was rapid and took only 1 to 2 days; however, it may have been affected by an intake of feces. The reticuloendothelial system was clearly delineated using a low dose of quantum dots in mice fed the purified diet. On the other hand, intestinal autofluorescence was visible 24 hours postinjection in mice given the alfalfa-free diet and definitely impaired the image quality in mice fed the regular diet. The use of a low-fluorescence diet, especially a purified diet, rapidly reduces intestinal autofluorescence and is expected to enhance the potential of in vivo FLI.